AN ANALYSIS OF MAXIMS VIOLATION ON TEACHER- STUDENTS INTERACTION IN THE ENGLISH CLASSROOM AT CITRA KASIH ELEMENTARY SCHOOL IN AMBON - Soumahu, Wisye; Lekatompessy, Felicia; Rijoly, Helena (Pattimura University, 2024)
This study aims to find the types of maxims violated by students and to investigate the factors that influence the violation of these maxims in classroom interaction. This study applied descriptive qualitative as the research method to collect the data through observation and interview from class V of Citra Kasih Elementary School in Ambon. The results from data collection showed that violations of maxims did exist during the classroom interaction, the types of maxims it could be concluded that the types of maxims violated by teachers and students were maxim of relevance with 5 times, maxim of manner with 5 times and maxim of quality with 4 times, while for the type of maxim of quantity was not found in the observation. It was obvious when students gave ambiguous or irrelevant answers or utterances and inaccurate or incorrect answers. The analysis of these findings indicated several factors that led to the maxim violation in classroom interactions, namely lack of vocabulary which is caused by the lack of self-exploration, social distance and cultural factors where students are not encouraged to discover and explore their knowledge, abilities and interests. Knowing these factors may help the teachers to anticipate possible factors that may hidding the effectiveness of classroom interaction. Therefore, it is suggested that embracing cooperative principles as framework of communication is considered beneficial to create meaningful and effective conversation which can avoid misunderstanding and misinterpretation between teacher -students.